ОСОБЕННОСТИ ГЕОЛОГИЧЕСКОГО СТРОЕНИЯ СРЕДНЕДЕВОНСКИХ ОТЛОЖЕНИЙ КУДИНОВСКО-РОМАНОВСКОЙ ПРИПОДНЯТОЙ ЗОНЫ - Чижов С.И.; Даньшина Н.В. (My University, 2003)
Приводится характеристика эйфельско-живетских отложений и выделяются различные типы органогенных построек. Прослежено их изменение снизу вверх по разрезу.

The paper deals with the characteristic of the Eifelian-Givetian deposits and various types of organogenic structures that have been determined. The change of organogenic structures in the upward direction has been also traced.
Keywords: Givetian; Eifelian; 551.1/4;551.734(470.45); Paleozoic::Devonian::Middle::Givetian; Палеозой::Девонская::Средний::Живетский; Paleozoic::Devonian::Middle::Eifelian; Палеозой::Девонская::Средний::Эйфельский